PENGGUNAAN MEDIA VLOG (VIDEO BLOG) UNTUK MENUMBUHKAN KEMAMPUAN PEMAHAMAN KONSEP SPLDV PESERTA DIDIK - Irma Nuryta Prisa; Dede Suratman; Asep Nursangaji (Universitas Tanjungpura, 2021)
AbstractThe study was conducted to investigate the relationship between the use of vlog media in learning and the concept understanding ability. The results of daily test of students who can achieve or exceed the Minimum Completeness Criteria are only 31.4% illustrating the lack of the understanding of students concepts. Using vlogs can be a choice of interactive and interesting learning media to help increase concept understanding of students. This type of research is explanatory research with selected research subjects are students of the 2019/2020 school year class VIII F according to the teacher's considerations. The research instrument was an essay test of concept understanding ability and a questionnaire of the use of vlog media in learning. The research analysis includes a description of the achievement of concept understanding, the feasibility of vlog learning media, and the Spearman Rank (ρ) test. The analysis results shows that the use of vlog media in learning has a relationship to the concepts understanding ability with a known correlation value of 0.410 which indicates the use of good vlogs as a learning medium sufficiently supportive to increase the ability to understand concepts.Keywords: Concept Understanding Ability, Learning Media, Vlog